2014
DOI: 10.1021/jp5047003
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Mechanisms and Equation of State of Methane Adsorption in Carbon Nanopores

Abstract: Adsorption is an important issue both in the estimation of natural gas reserves and efficient storage of methane. In this study, we focus on the mechanisms of methane adsorption in carbon nanopores and endeavor to establish the equation of state for the adsorbed phase through molecular dynamics simulations and theoretical analyses. Here, the nanopores were modeled by carbon nanotubes (CNTs). The higher storage capacity of the CNT compared to the bulk phase was attributed to the additional pressure exerted by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 24 publications
1
69
2
3
Order By: Relevance
“…At this nanometer scale, MD simulation implemented in LAMMPS package is a reliable and efficient method. 29,30 Fig. 2 shows the schematic representation of our simulation model.…”
Section: Simulation Models and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this nanometer scale, MD simulation implemented in LAMMPS package is a reliable and efficient method. 29,30 Fig. 2 shows the schematic representation of our simulation model.…”
Section: Simulation Models and Methodsmentioning
confidence: 99%
“…Because of the adsorption effect, methane content in shale gas reservoir usually exceeds the conventional estimation. 29,30 For methane molecules far away from the walls, they are stored in the bulk state and the density nearly keeps constant. The value of bulk density obtained from our EMD simulations agrees well with that obtained from the National Institute of Standards and Technology (NIST), which can validate the accuracy of our simulation methods.…”
Section: A the Static Properties Of Methane In Nanoporesmentioning
confidence: 99%
“…And they reported that there is an optimum pore size that maximizes the excess adsorption [15]. Zhu and Zhao investigated the atomic mechanisms of CH 4 adsorption in carbon nanopores and established the equation of state for the adsorbed phase [25].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption behavior of oil within nanoscale carbonaceous slits of shale systems was studied by using MD simulation, with graphene sheets as the model of shale [28]. Recently, the atomic mechanisms and adsorption properties of CH 4 tigated [29][30][31][32]. Graphene is widely used in the researches of shale and coal.…”
Section: Introductionmentioning
confidence: 99%